2007
DOI: 10.4049/jimmunol.179.10.6536
|View full text |Cite
|
Sign up to set email alerts
|

IL-1α and IL-1β Are Endogenous Mediators Linking Cell Injury to the Adaptive Alloimmune Response

Abstract: Preoperative or perioperative ischemic injury of allografts predisposes to graft arteriosclerosis, the major cause of late graft failure. We hypothesize that injured tissues release mediators that increase the production of pathogenic cytokines by alloreactive T cells. We find that freeze-thaw lysates of human endothelial cells (EC) increase both IFN-γ and IL-17 production by human CD4+ T cells activated by HLA-DR+ allogeneic EC. Immunoadsorption of high-mobility group box 1 protein (HMGB1) reduces this activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 85 publications
7
85
0
2
Order By: Relevance
“…3,28 Activated neutrophils have been suggested to have significant implications in the pathogenesis of allograft rejection. 32 Combining our observations together with others, 31 we propose that Th17 alloreactive response provides a rapid influx of neutrophils into the grafts, which then mediate early graft damage when the development of IFN-g-producing T cells is still at the early stage. However, once these IFN-g-producing T cells are dominant at the late stage of rejection, resulting in the influx of monocyte/macrophages into the grafts, the actions of IL-17-producing T cells are then receded to a relatively low level.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…3,28 Activated neutrophils have been suggested to have significant implications in the pathogenesis of allograft rejection. 32 Combining our observations together with others, 31 we propose that Th17 alloreactive response provides a rapid influx of neutrophils into the grafts, which then mediate early graft damage when the development of IFN-g-producing T cells is still at the early stage. However, once these IFN-g-producing T cells are dominant at the late stage of rejection, resulting in the influx of monocyte/macrophages into the grafts, the actions of IL-17-producing T cells are then receded to a relatively low level.…”
Section: Discussionsupporting
confidence: 75%
“…Interestingly, HMGB1 functions by inducing IL-1b secretion from monocytes through TLR4 and CD14. 31 Our data indicate that HMGB1 also enhances Th17 alloreactive response by inducing IL-6 production from DCs. It has been shown that IL-17 acts as a potent proinflammatory cytokine to induce tissue damage at least in part through neutrophil recruitment.…”
Section: Discussionmentioning
confidence: 62%
“…producing, CD4+ Th cells [18] and IL-17/Th memory cell populations [19]. Due to measuring proliferation after only 48h, our studies show that there is a rapid effect of IL-36β which cannot be due merely to increased survival as has been shown in some other studies mentioned above.…”
Section: Discussionsupporting
confidence: 63%
“…These mediators include some of the cytokines that are important in T cell differentiation such as TGFβ (Basile et al 2001). A recent study demonstrated that factors released by human endothelial cells as a consequence of ischemia-reperfusion injury could enhance the production of both IL-17 and IFNγ by CD4 + T cells (Rao, Tracey, and Pober 2007). These findings indicate that perioperative factors might result in increased Th17 activity within the graft.…”
Section: Il-17 In Transplantationmentioning
confidence: 99%